Characterisation of bovine serum albumin-based biomaterials synthesised by subcritical water technology - Esfahan, Zahra Maghareh (2019)
Bovine serum albumin (BSA), is one of the most abundant proteins in mammals’ blood, especially from bovine and human. This study investigated the synthesis and characterization of BSA-based biomaterials that was produced by subcritical water technology (SCWT). BSA is freely available and is a cheap source of protein to be recycled into various biomaterials. Using toxin and non-environmentally friendly chemicals is the main drawback of the current methods of biomaterials processes as well as long procedures time. Therefore, the primary goal of this study was to assess whether Subcritical Water can be used as a cheap, clean and simple alternative to the traditional recovery method to produce biomaterials from BSA. In addition, this is the first study ever analyzing ‘BSA’ biomaterials employing the simple and quick SCWT method without using any catalyst or chemicals. Although BSA solution decomposition at high SCWT temperature (above 2500C) and long SCWT holding time (5 mins and longer) was investigated wisely, we focused on low SCWT temperature (below 2500C) which provided indications that it could deliver valuable products as its high temperature treatment. The best conditions of processing biomaterials were identified by assessing the effect of different influential parameters such as SCWT temperature, reaction time, and initial BSA concentration. SCWT was carried out using a batch tube reactor to produce BSA-based biomaterials (BSA-based hydrogel and BSA-based nanoparticles). BSA molecules in temperature range of 80- 1200C accumulate to BSA-based hydrogel. It was found that at SCWT temperature more than 1300C, due to the water/ethanol mixture behavior of SCW, in very specific SCWT condition, accumulated BSA molecules decomposed to BSA-based nanoparticles and following by decomposing to organic components. The behavior of BSA-based hydrogel was investigated in different media wisely which confirmed that it has an excellent ability to use as drug delivery. By characterization of the BSAbased nanoparticles and liquid-phase components produced were conducted. In short, the result of this study showed that SCWT of BSA is the best method in terms of time, efficiency and quality of produced biomaterials as well as the method’s nondependence on catalyst or toxic chemicals. Low, medium and high SCWT temperature of BSA (80-2000C) was found to contain beneficial biomaterials useful for medical, especially drug delivery application.